2019
DOI: 10.1080/26395940.2019.1578187
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in response of lettuce (var. ramosa Hort.) to copper oxide nanoparticles/microparticles as potential agricultural fertilizer

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles Divergence in response of lettuce (var. ramosa Hort.) to copper oxide nanoparticles/microparticles as potential agricultural fertilizer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Furthermore, the nanoformulation could increase the bioavailability of soil nutrients to be absorbed by the plant root. The photosynthesis of Spinacia oleracea plants was enhanced when the soil was treated with CuO NPs at 200 mg/kg concentration after 60 days of application [63]. Along with the benefits offered by the nanoformulation as an herbicide in seed germination and foliar application, it significantly promoted the total chlorophyll and carotenoids in the soil application.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the nanoformulation could increase the bioavailability of soil nutrients to be absorbed by the plant root. The photosynthesis of Spinacia oleracea plants was enhanced when the soil was treated with CuO NPs at 200 mg/kg concentration after 60 days of application [63]. Along with the benefits offered by the nanoformulation as an herbicide in seed germination and foliar application, it significantly promoted the total chlorophyll and carotenoids in the soil application.…”
Section: Discussionmentioning
confidence: 97%
“…Foliar spraying of Nano Fe significantly increase protein content in Phaseolus vulgaris (Jahanara et al 2013). Wang et al (2019) Reported that the application CuO-NPs mixed with the soil were no significant change in Chl a content, intercellular CO 2 concentration or photosynthetic rate in leaves of lettuce while Cu-NPs @ 200 mg/kg were found Chl b in the lettuce leaves is decreased as compared with control. Cao et al (2018) revealed that the chlorophyll pigments were severely reduced by the excessive Cu (120 μM as CuSO 4 ) resulting the lower stomatal conductance and photosynthetic rate.…”
Section: Satdev and Mandalmentioning
confidence: 98%
“…To elucidate if the morphological and nuclear alterations of the gametogenesis of S. cerevisiae induced by CdS QDs were specific for these ENMs, the same sporulation assay was also carried out using other metal-based nanoparticles characterized by different chemical compositions, sizes, and zeta potentials (Figure S1): ZnS QDs, to evaluate QDs with a different metal composition; CuO NPs, to evaluate ENMs with potential applications from biomedicine to agriculture [34][35][36], but for which several studies have reported toxicity in different organisms [37][38][39]; and CeO2 NPs, to evaluate ENMs with very low toxicity, which in yeast have been shown to inhibit toxicity induced by α-synuclein in a yeast model of Parkinson's disease [40]. We have observed that even at much higher doses than those used for CdS QDs, none of these ENMs significantly affected the sporulation process in S. cerevisiae (Figure 4).…”
Section: Cds Qds Strongly Affect the Sporulation Processmentioning
confidence: 99%